DESCRIPTION OF POLYMORPHIC VARIANTS OF NUCLEAR TRANSCRIPTION FACTOR NF- KB1 AS PREDICTORS OF GENERALISED PERIODONTITIS DEVELOPMENT - N. V. Gasyuk (Bogomolets National Medical University, 2016)
Summary. In the article results of molecular genetic studies of pathogenetic mechanisms of inflammatory diseases periodontal tissues through polymorphism nuclear transcription factor NF-kB1, which controls the expression of immune response genes, apoptosis and cell cycle. The data make it possible to state that certain polymorphic variants of the gene NF-kB1 enable the formation of groups at risk of morbidity of generalized parodontitis. The contingent of people with genotype (Del/Del) to recommend under medical observation. Persons with polymorphic variant of NF-kB1 (Del/Ins) constitute risk in the event of bad habits and concomitant somatic pathology that are predictors for the development of general parodontitis induced vascular disorders against the background of lamina propria gums. Persons with polymorphic variant of NF-kB1 (Ins/Ins), constitute a risk group in case of adverse impact of local factors and existing teeth-jaw abnormalities and deformities. Adjusted distribution of polymorphic variants enables timely prediction and prevention of generalized periodontitis